(3SdWI GdbGVj GdJbOjQjI aj GdehGO GdeOfjI h GdJLGQjI (B:s (3OQGSI JMdjdjI hJWHjbjI (B/s - (3YeQ, fHjd GSeGYjds ((3GdEScfOQjI(B: s (3OGQ GdLGeYI GdLOjOI ddfTQ(B, s, 2002)
(3JLO aj gPG GdcJGH (B: (3aj eaghe GdSdWI GdJbOjQjI HhLg YGe , eGgjI GdJbOjQ GdehVhYj GdbVGFj , eGgjI GdJbOjQ GdTNUj aj GdYed GdbVGFjs
(3GdeQGLY U(B.540s
Keywords: (3GdSdWIs; (3GdbGfhfs